THE ROLE OF A UNIVERSITY IN A CHANGING WORLD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PUTRAJAYA, 1 December 2015 – Universities at present, need to be open to welcome discussions, need to continue in allowing and encouraging minds to enquire, need to innovate and create, need to reduce the inequity divide, need to ensure accessibility to higher education and need to play a major role in the commercialisation of ideas.